Liberia Tertiary Education : SABER Country Report 2017 - World Bank Group (World Bank, Washington, DC, 2017)
SABER-Tertiary Education is a diagnostic tool to assess how education systems perform and to identify priorities for reforms at the national level. It is part of the World Bank’s Systems Approach for Better Education Results (SABER), which aims to benchmark education systems at the country level. This report proceeds as follows. First, the authors will describe the context of the tertiary education system in Liberia. The authors will then proceed with a summary of the considerations when scoring the six policy dimensions. Finally, the authors will conclude with a few general observations about tertiary education in Liberia.